MOTIVASI, PERSEPSI DAN KONFLIK PERAN PEKERJAAN-KELUARGA ENTREPRENEUR PEREMPUAN DAERAH ISTIMEWA YOGYAKARTA - Ummu Harmain; Slamet Hartono; Lestari Rahayu W; Dwidjono H.D Dwidjono H.D (Universitas Muhammadiyah Purwokerto, 2014)
This research is conducted to determine the motivations, perceptions and work-family role conflict of women entrepreneurs. Respondents are about 159 women entrepreneur of processed food in Daerah Istimewa Yogyakarta. This research uses descriptive qualitative analysis. The results show that most of their motivations to be entrepreneur are because of external factors in which financial pressure as the main reason. All the business environments observed, namely access to capital and credit, market orientation, networks and government support are in good atmosphere. Women entrepreneur have work-family conflict primarily related to the division of domestic labor, lack of work flexibility and the solid work hours. Keywords: women entrepreneur, motivations, perceptions and work-family role conflict.